Determination of Coronary Failure with the Application of FFT and AR Methods - Serhatlio?lu, Selami; Burma, Oktay; Hardalaç, Firat; Güler, Inan (My University, 2003)
In this study, Doppler signals recorded from the output of carotid artery of 30 patients were transferred to a personal computer (PC) by using a 16-bit sound card. Doppler difference frequencies were recorded from each of the patients, and then analyzed using fast Fourier transform (FFT) and least squares autoregressive (AR) methods to obtain their sonograms. These sonograms are then used to compare with the applied methods in terms of medical evaluation.
Keywords: Carotid artery; Doppler signal; Signal analysis; Sonogram